Dispersion Measurements for Underground Hydrogen Storage over Sequestered CO2 - Sam Kobeissi; Nicholas N. A. Ling; Minzhen Li; Eric F. May; Michael L. Johns (Transport in Porous Media, 2026)
Underground hydrogen storage (UHS) in depleted gas reservoirs is an effective strategy for balancing renewable energy supply and demand, with cushion gases being used to maintain storage pressure. Here CO 2 is investigated as a cushion gas via measurements of the dispersion between hydrogen and CO 2 in a (Bentheimer sandstone) rock core, performed at reservoir-relevant conditions using a novel core flooding apparatus. Such data is required to quantify undesirable mixing between the stored hydrogen and the cushion gas. Dispersion coefficients ( K L ) were measured at 50–100 bar and 22–60 °C, with injection velocities up to 170 m/day, employing benchtop NMR spectroscopy for effluent composition analysis. The value of K L ranged from 0.018 to 0.06 m 2 /day, with most of the measurements performed for H 2 extraction (CO 2 displacing H 2 ). At 22 °C and 50 bar, a representative comparison showed higher dispersion during H 2 injection (H 2 displacing CO 2 ) than during H 2 extraction. This behaviour is attributed to the viscosity ratio (ratio of displaced to displacing fluid) exceeding unity during H 2 injection, promoting viscous fingering. Extrapolation of K L to its value at minimal flow velocity produced a tortuosity value that ranged from 2.24 to 2.63 depending on the diffusion coefficient used, which was consistent with the independent measurement of 2.32 ± 0.20 produced using pulse field gradient (PFG) NMR measurements. Values of the molecular diffusion coefficient ( D 12 ) estimated using Thorne-Enskog theory resulted in the normalised K L / D 12 data collapsing onto a single curve for all of the temperature and pressure conditions considered.

Morpho-physiological and molecular responses of Capsicum species to abiotic stresses - Nurin Izzah Fairuzamizi; Weng-Sam Lai; Nur Fatihah Mohd Yusoff; Chai-Ling Ho (Journal of Plant Biochemistry and Biotechnology, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

The Shu complex is an ATPase that regulates Rad51 filaments during homologous recombination in the DNA damage response - Sam S.H. Chu; Guangxin Xing; Vikash K. Jha; Hong Ling (DNA Repair, 2025)

Bio-physical determinants of sediment accumulation on an offshore coral reef: A snapshot study - Sterling B. Tebbett; Jodie A. Schlaefer; Casey L. Bowden; William P. Collins; Christopher R. Hemingson; Scott D. Ling; Juliano Morais; Renato A. Morais; Alexandre C. Siqueira; Robert P. Streit; Sam Swan; David R. Bellwood (Science of The Total Environment, 2023)

Synergistic interactions between sewage sludge, polypropylene, and high-density polyethylene during co-pyrolysis: An investigation based on iso-conversional model-free methods and master plot analysis - Crystal Chia Yin Ling; Sam Fong Yau Li (Journal of Hazardous Materials, 2023)

Ocean acidification increases inorganic carbon over organic carbon in shrimp's exoskeleton - Veran Weerathunga; Chin-Chang Hung; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Kai-Jung Kao; Kuei-Chen Huang; Wei-Jen Huang (Marine Pollution Bulletin, 2023)

Impacts of pH on the Fitness and Immune System of Pacific White Shrimp - Veran Weerathunga; Wei-Jen Huang; Sam Dupont; Hsueh-Han Hsieh; Nathangi Piyawardhana; Fei-Ling Yuan; Jhe-Syuan Liao; Chia-Yu Lai; Wei-Ming Chen; Chin-Chang Hung (Frontiers in Marine Science, 2021)
The atmospheric partial pressure of CO 2 ( p CO 2 ) has been increasing dramatically since the beginning of the industrial revolution and about 30% of the CO 2 produced by anthropogenic activities was absorbed by the ocean. This led to a perturbation of the seawater carbonate chemistry resulting in a decrease of the average surface ocean pH by 0.1 and termed ocean acidification (OA). Projections suggest that p CO 2 may reach 900 μatm by the end of the twenty-first century lowering the average pH of the surface ocean by 0.4 units. The negative impacts of OA on many species of marine invertebrates such as mollusks, echinoderms, and crustaceans are well documented. However, less attention has been paid to the impacts of low pH on fitness and immune system in crustaceans. Here, we exposed Pacific white shrimps to 3 different pHs (nominal pH 8.0, 7.9, and 7.6) over a 100-days experiment. We found that, even though there were no significant effects on fitness parameters (survival, growth and allometries between length and weight), some immune markers were modified under low pH. A significant decrease in total hemocyte count and phenoloxidase activity was observed in shrimps exposed to pH 7.6 as compared to pH 8.0; and phagocytosis rate significantly decreased with decreasing pH. A significant increase in superoxide production was also observed at pH 7.6 as compared to pH 8.0. All these results suggest that a 100-days exposure to pH 7.6 did not have a direct effect on fitness but lead to a modulation of the immune response.

Communicating Uncertainty in Climate Information for China: Recommendations and Lessons Learned for Climate Services - Andrea Louise Taylor; Sam Grainger; Suraje Dessai; Yim Ling Siu; Marta Bruno Soares (Journal of Meteorological Research, 2021)

A review of the mechanisms by which attentional feedback shapes visual selectivity - Sam Ling; Janneke F. M. Jehee; Franco Pestilli (Brain Structure and Function, 2015)

Implementation of a Reference-Scaled Average Bioequivalence Approach for Highly Variable Generic Drug Products by the US Food and Drug Administration - Barbara M. Davit; Mei-Ling Chen; Dale P. Conner; Sam H. Haidar; Stephanie Kim; Christina H. Lee; Robert A. Lionberger; Fairouz T. Makhlouf; Patrick E. Nwakama; Devvrat T. Patel; Donald J. Schuirmann; Lawrence X. Yu (The AAPS Journal, 2012)

Genetic structure of a recent climate change-driven range extension - SAM C. BANKS; SCOTT D. LING; CRAIG R. JOHNSON; MAXINE P. PIGGOTT; JANE E. WILLIAMSON; LUCIANO B. BEHEREGARAY (Molecular Ecology, 2010)

Inhibition of the CXCR4/CXCL12 chemokine pathway reduces the development of murine pulmonary metastases - Su Young Kim; Chih Hung Lee; Brieanne V. Midura; Choh Yeung; Arnulfo Mendoza; Sung Hyeok Hong; Ling Ren; Donald Wong; Walter Korz; Ahmed Merzouk; Hassan Salari; Hong Zhang; et al. (Clinical & Experimental Metastasis, 2008)

Bioequivalence Approaches for Highly Variable Drugs and Drug Products - Sam H. Haidar; Barbara Davit; Mei-Ling Chen; Dale Conner; LaiMing Lee; Qian H. Li; Robert Lionberger; Fairouz Makhlouf; Devvrat Patel; Donald J. Schuirmann; Lawrence X. Yu (Pharmaceutical Research, 2008)